A review on the tensile behavior of fiber-reinforced polymer composites under varying strain rates and temperatures. (2nd August 2021) - Ahmed, Azzam; Zillur Rahman, Md; Ou, Yunfu; Liu, Sai; Mobasher, Barzin; Guo, Shuaicheng; Zhu, Deju
Highlights: Tensile strength depends on strain rates, temperatures, and coupling effects. FRP composites are temperature sensitive due to the resin's softening. FRP composites highly depend on reinforcement and resin properties. Fiber breakage and fiber pullout become dominant at low and high strain rates, respectively. Abstract: The fiber-reinforced polymer (FRP) composites are currently widely used in infrastructure construction, and the study on the dynamic performance and temperature sensitivity is still under investigation. Understanding the effects of strain rate and temperature on the tensile behaviour of FRP composites is vital to design the composite structures under harsh conditions (earthquake, explosion, or impact). Therefore, this study comprehensively reviews tensile performance of FRP composites under several strain rates (quasi-static, low, intermediate, and high) and temperatures. The tensile strength of FRP composites depends on the strain rates, temperatures, and coupling effect. The failure patterns of FRP materials are also reviewed at different strain rates and temperatures and found that fiber cracking and fiber pullout become dominant at low and high strain rates, respectively, which can help gain insight into failure mechanisums of FRP composites.